MOOCS, THE PLATFORM TO PROMOTE GLOBAL KNOWLEDGE-SHARING - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 27 February 2016 – Having started the first Massive Open Online Course (MOOCs) ‘classroom’ in Malaysia, Professor Dr. Mushtak AlAtabi, Dean of School of Engineering from Taylor’s University, was a truly passionate and creative practitioner of his art.